Cover Image, Volume 29, Issue 6. Issue 6 (June 2017) - Ogino, Yoshiyuki; Tanaka, Masahito; Shimozawa, Togo; Asahi, Toru
Abstract : The cover image, by Yoshiyuki Ogino et al., is based on the Regular Article LC–MS/MS and chiroptical spectroscopic analyses of multidimensional metabolic systems of chiral thalidomide and its derivatives, DOI:10.1002/chir.22683 .